Diagnosis and treatment of 33 patients with primary melanoma of the female reproductive system - Gao, Yunge; Dong, Jian; Chen, Ligang; Guo, Xin; Liu, Lingling; Guo, Weinan; Ma, Cuiling; Chen, Biliang; Wang, Jian; Lv, Xiaohui (Frontiers in Oncology, 2025)
ObjectiveThis study aims to investigate the clinical and pathologic characteristics, treatment, and prognosis of primary melanoma in the female reproductive system.MethodsA retrospective analysis was performed using the clinical and pathological data of 33 patients with melanoma of the female lower genital tract who presented at the Department of Gynecology at Xijing Hospital of Air Force Military Medical University between June 2006 and July 2022. Pathological review and immunohistochemical staining were performed in all cases to confirm the diagnosis.ResultsA total of 15 (45%) cases of primary melanoma involved the vulva, 16 (49%) involved the vagina, and two (6%) involved the cervix. The HMB-45 positive rate was 93%, the S-100 positive rate was 90%, and the Vim positive rate was 100%. Of these 33 cases, we had complete clinical information on 27 of them who received various comprehensive treatments including surgical treatment, postoperative radiotherapy, chemotherapy, immune therapy, or targeted therapy. Patients with stage III–IV comprised 67% of all cases, and the average duration of follow-up was 24 months. The 2-year recurrence rate was 82%, and the 3-year overall survival rate was 42%.ConclusionsThe incidence of melanoma in the female reproductive system is low, and the prognosis is poor owing to the difficulty of early diagnosis and the high possibility of metastasis. Individualized comprehensive treatment like surgical treatment combined with immunotherapy can prolong the survival time and improve the prognosis of patients.